Entrepreneurship Education: A Global Evaluation of Entrepreneurial Attitudes and Values (a Transcultural Study) - Valeria Caggiano; Humphrey Akanazu; Angela Furfari; Andrew Hageman (LED Edizioni Universitarie, 2016)
Entrepreneurship education is a new phenomenon in higher education, as a field of inquiry it is one of the most rapidly growing areas of research (Katz, 2008).The paper includes the analyses of the different entrepreneurial attitudes of Nigerian students in comparison with that of the Italian students. The related entrepreneurship education literatures make references towards exploring entrepreneurial attitudes and the values perceptions of Nigerian and Italian students. The findings suggest a considerable socio-cultural impact: one that starts with values and religion support and extends to the attitudes itself and on entrepreneurs' access to entrepreneurship education (Chen, 2005). Building from these analyses, a theoretical paradigm for the growth of entrepreneurship education is offered, using the applied research as the example. The contribution of this article suggests the necessity to design and implement a curriculum which provides a systematic teaching of the entrepreneurial attitudes and values in the institutions of learning as a whole. The article seeks to contribute to a growing need to find innovative ways of thinking and develop entrepreneurial approaches to education.